Pro Git - Chacon, Scott (Expert's voice in software development., 2009)
"Programmers or project leaders will learn to use Git, the version control system developed by Linus Torvalds for Linux kernel development. You'll discover the world of distributed version control and learn how to build a Git development workflow, with expert guidance from Scott Chacon"--Resource description page